Confirmatory Factor Analysis of Sleep Model’s Questionnaires - Pinto, Teresa Rebelo (2016)
Objectives: The present study aims to test the factor structure of two sleep questionnaires and their internal consistency in a sample of adolescents and their respective parents and to evaluate the validity and robustness of a three-dimensional model about sleep, addressing nine subcategories related to sleep habits, personal and environmental factors (Rebelo-Pinto, Pinto, Rebelo-Pinto, & Paiva, 2014). Methods: Participants were 654 adolescents from Portuguese schools, who completed “My Sleep and I” questionnaire, and 664 parents who completed “My child’s sleep” questionnaire; to them confirmatory factor analysis was applied. Results: Confirmatory factor analysis indicate that a nine-factor model has better fit indices compared with the others tested models for both samples (Adolescents: X2/df (chi-square/degrees of freedom)= 2.59, CFI (Comparative Fit Index)=.82, GFI (Goodness-of-Fit Index)=.92, RMSEA (Root Mean Square Error of Approximation)=.049, ECVI (Expected Cross-Validation Index)= 1.416; Parents: X2/df= 2.89, CFI=.85, GFI=.91, RMSEA=.053, ECVI= 1.528). Moreover, the comparison of the models through Δχ² index (chi-square difference between rival models) indicates a better fit for this model, Δχ² (24) = 186.5, p < .001 for adolescents and Δχ² (24) = 209, p < .001 for parents. Also, the three second-order factors have good internal consistency, convergent and discriminant validity for all factors in both samples. Conclusions: Results postulate that the three factors and their nine subcategories account for correlations between sleep habits, self-perceptions and knowledge about sleep.